Internal Medicine Residents' Views About Care Transitions: Results of an Educational Intervention. (January 2021) - Sheikh, Fatima; Gathecha, Evelyn; Arbaje, Alicia I; Christmas, Colleen
Problem: Suboptimal care transitions can lead to re-hospitalizations. Intervention: We developed a 2-week "Transitions of Care Curriculum" to train first-year internal medicine residents to improve their knowledge and skills to deliver optimal transitional care. Our objective was to use reflective writing essays to evaluate the impact of the curriculum on the residents. Methods: The rotation included: Transition of Care Teaching modules, Transition Audit, Transitional Care Site Visits, and Transition of Care Conference. Residents performed the above elements of care transitions during the curriculum and wrote reflective essays about their experiences. These essays were analyzed to assess for the overall impact of the curriculum on the residents. Qualitative analysis of reflective essays was used to evaluate the impact of the curriculum. Of the 20 residents who completed the rotation, 18 reflective essays were available for qualitative analysis. Results: Five major themes identified in the reflective essays for improvement were: discharge planning, patient-centered care, continuity of care, goals of care discussions, and patient safety. The most discussed theme was continuity of care, with following subthemes: fragmentation of the healthcare system, disjointed care to the patients, patient specific factors contributing to lack of continuity of care, lack of primary care provider role as a coordinator of care, and challenges during discharge process. Residents also identified system-based gaps and suggested solutions to overcome these gaps. Conclusions: This experiential learning and use of reflective writing enhanced the residents' self-identified awareness of gaps in care transitions and prompted them to generate ideas for systems improvement and personal actions to improve their practice during care transitions.